2022
DOI: 10.1109/jeds.2022.3144530
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multi-Scale Method for Thermo-Mechanical Simulation of Power Integrated Circuits

Abstract: During development of power IntegratedCircuits (IC), several iterations between the design and test/ measurement steps are performed. Computer-aided engineering significantly shortens the product development process because the numerical simulations can identify and remediate most deficiencies during the design stage. The recent IC manufacturing technologies lead to ca. 10 4 -order scale separation between transistor cell details and the device active area, resulting in very complex IC models. For the IC compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In conclusion, the width, the length, the density, and the grouping of the thin metal lines used as IMD cracking sensors can be conveniently adjusted in order to detect the desired failure mechanism while preserving a reasonable amount of the device metallization reliability. In order to make an assessment regarding an adequate placement of the sensors, the results of the thermo-mechanical simulations presented in [ 10 , 27 ] were taken into consideration. The simulations were carried out on almost identical metallization structures and the simulated stress and strain distributions suggested that the maximum plastic strain accumulation takes place in TTML, right underneath the PM bottom edge (along the XX’ axis in Figure 2 a).…”
Section: The Test Chipmentioning
confidence: 99%
“…In conclusion, the width, the length, the density, and the grouping of the thin metal lines used as IMD cracking sensors can be conveniently adjusted in order to detect the desired failure mechanism while preserving a reasonable amount of the device metallization reliability. In order to make an assessment regarding an adequate placement of the sensors, the results of the thermo-mechanical simulations presented in [ 10 , 27 ] were taken into consideration. The simulations were carried out on almost identical metallization structures and the simulated stress and strain distributions suggested that the maximum plastic strain accumulation takes place in TTML, right underneath the PM bottom edge (along the XX’ axis in Figure 2 a).…”
Section: The Test Chipmentioning
confidence: 99%